Possible mechanisms of DNA demethylation in blood of patients with type 2 diabetes (2017)
"Type 2 Diabetes Mellitus (T2DM) is a complex disease characterized by hyperglycemia and increased oxidative stress that could lead to chronic micro- and macro-vascular complications. In this study, we analyze the epigenetic effects of diabetes in blood cells of patients and controls and the molecular causes that could originate these alterations". -- Tomado de la introducción.